Prospects for the use C02 in oil and Gas Fields in Western Siberia - R. M. Galikeev; D. A. Anuriev; T. A. Kharitonova (Наука. Инновации. Технологии)
Introduction: The paper considers the world experience of using CO2 as a displacing agent in oil fields. An analytical assessment of determining the minimum mixing pressure for the conditions of Western Siberia has been carried out. Materials and methods of the research: The world experience of using CO2 as an agent for displacement of residual recoverable reserves is described. The possibility of application based on empirical dependencies is estimated. The results of the study and their discussion: The results of the analysis of the development of enhanced oil recovery methods, in particular gas methods with the use of CO2, are presented. The results on additional oil production from the use of gas methods and the geography of distribution of these methods are presented. The main empirical relationships have been determined and a preliminary assessment of the applicability of CO2 as a displacing agent has been carried out to increase oil recovery. Potential gas suppliers have been identified based on large CO2 sources in Russia. Conclusions: Recently, in connection with global warming, technologies for reducing CO2 emissions, based on capturing industrial emissions and further using this gas as a displacing agent, have been developing in the world. The use of gas methods to enhance oil recovery on the territory of the Russian Federation is relatively small compared to other methods, and we can expect the emergence of new projects for CO2 injection into the reservoir, using industrial emissions as a source of this gas.